How do I structure logistic processes in preparation for outsourcing of cellular therapy manufacturing?. Issue 8 (28th May 2019) - Chen, Leonard N.; Collins‐Johnson, Naoza; Sapp, Nasheda; Pickett, Angela; West, Kamille; Stroncek, David F.; Panch, Sandhya R.
Abstract : As cell and gene therapies (CGT) assume center stage in early‐phase clinical trials for several acute and chronic diseases, there is heightened interest in the standardization and automation of manufacturing processes in preparation for commercialization. Toward this goal, a hybrid and oftentimes geographically separated model comprising regional cell procurement and infusion facilities and a centralized cell manufacturing unit is gaining traction in the field. Although CGT processing facilities in academic institutions are not involved directly in the manufacturing of these therapies, they must be prepared to collaborate with commercial or contract manufacturing organizations (CMOs) and be ready to address several supply‐chain challenges that have emerged for autologous and allogeneic CGT. Academic center cell‐processing facilities must handle many events up‐ and downstream of manufacturing such as donor screening, cell collection, product labeling, cryopreservation, transportation, and thaw infusion. These events merit closer evaluation in the context of multifacility manufacturing since standard procedures have yet to be established. Based on our institutional experience, we summarize logistical challenges encountered in the handling and distribution of CGT products in early phase studies, specifically those involving CMO (outsourced) manufacturing. We also make recommendations to standardize processes unique to the CGT supply chain, emphasizing the need to maintain needle‐to‐needle traceability from product collection to infusion. These guidelines will inform the development of more complex supply‐chain models for larger‐scale cell and gene therapeutics.